ADHERENCE TO CUPPING PRACTICE GUIDELINES AMONG CUPPING PRACTITIONERS IN MALAYSIA - Mahat, Nur Ain; Rahman, Zairina Abdul (International Journal of Psychosocial Rehabilitation, 2020)
Bekam (or cupping) practice guideline has been published by Traditional and Complementary Medicine Division Ministry of Health Malaysia, first edition of 2011, mainly to focus on proper handling of patients and clinical wastes to ensure safety of both practitioners and patients, in supplementary of optimizing patient care. This cupping practice guideline covers treatment criteria, treatment procedures, documentations and practice facilities. However, there is a scarce research revealing this issue as currently there are profuse emergences of blood borne infection diseases such as HIV/AIDS, Hepatitis B and C due to its invasiveness. Therefore, this study aimed to determine adherence towards practice guidelines among cupping practitioners in Malaysia, as well as to identify factors associated with it. A cross sectional study with random sampling was conducted among 114 cupping practitioners from all over Malaysia using self-administered adherence to practice guideline questionnaire, which consisted of 18 items with 5 Likert scales ranging from “never” to “very often”. “Adherence to practice guideline” in this study is defined as practitioners who scored 90 marks to all 18 components of standard precautions in practice guidelines with cut-off point of 90. The mean age was 38 years old with majority of them were male (64.9%), Malay (99.1%), degree holder with various background (27.8%) and part timer (69.9%). Mean duration of working experience was 4 years. A total of 45.6% of respondents attended cupping training from as short as 1 day to 3 years in getting their certificate. Adherence to practice guideline among respondents was 5.3%. The highest adhered practice was wearing gloves during treatment (86.0%), while the lowest was documenting the estimated amount of blood that was released during cupping (19.4%). Multiple linear regression revealed part timers were less adhered to practice guideline as compared to full timers (P